Strengthening Educational Quality through Parental Engagement in Islamic Primary Education: Evidence from a Madrasahh Context - Sumarsono, Raden Bambang; Imron, Ali; Wiyono, Bambang Budi; Arifin, Imron (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
One of the primary determinants of students' academic achievement is parental involvement, which encompasses various forms such as emotional support, academic supervision, and participation in school activities. Previous studies have shown that (1) parental involvement has a significant positive correlation with students' academic performance, and (2) parent-school interaction contributes to an increase in student motivation. However, most of these studies have primarily focused on public schools and have not sufficiently addressed the context of religiously based Education, such as madrasahs. In reality, Education in madrasahs presents different challenges and characteristics, including the implementation of a dual curriculum (religious and general), unique social relationship patterns, and diverse forms of community participation. Therefore, this study aims to examine (1) the forms of parental involvement in supporting the improvement of Education quality in madrasahhs, and (2) the strategies employed by madrasahhs to encourage active parental involvement. This research uses a qualitative research design with a multi-case approach. The research subjects are state and private madrasah ibtidaiyah (Islamic elementary schools) located in the city of Malang. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was followed by within-case and cross-case analysis stages using the constant comparative method. The research results indicate that: (1) the forms of parental involvement in supporting the improvement of Education quality in madrasahhs include: (a) donating livestock for Eid al-Adha celebrations, (b) family gatherings, (c) cooking class activities, (d) providing ideas or suggestions for program planning, (e) participation in Outing Class activities, (f) assisting children with studying at home, and (g) going beyond just homework help. (2) The strategies used to encourage parental involvement include: (a) creating a conducive school environment, (b) involving parents in the planning, implementation, and monitoring of school activities, (c) establishing intensive communication, (d) implementing principles of transparency and accountability in the execution of school programs, (e) designing school activities that benefit parents, and (f) fostering a positive attitude among all school members towards students and their parents.